Overview of spittlebugs of the family Cercopidae (Hemiptera: Auchenorrhyncha) from Mexico, with keys to genera and species - Francisco Armendáriz-Toledano; Misael Adrián López-Posadas; Vinton Thompson; Jesús Romero-Nápoles; Youssef Utrera-Vélez; Juan Pedro López-Córdova; Ulises Castro-Valderrama (Revista Mexicana de Biodiversidad)
The Cercopidae family constitute the largest group of xylem sap-sucking insects. Several species are important pests of sugar cane and grasses. In America there are 460 species and 65 subspecies in 60 genera. In Mexico, the total number of species is unknown and there is no inventory of specimens in the collections or taxonomic keys. In the present research, we study entomological collections to trace the distribution of genera and species and constructed taxonomic keys for their identification, based on external morphology and male genitalia. The Cercopidae of the country included 3 recognized tribes, Neaenini Fennah, 1968, Ischnorhinini Schmidt, 1920 and Tomaspidini Schmidt, 1922, in addition to the recently proposed Microsarganini Hamilton, 2016. We reported 39 described species, 1 subspecies and 1 undescribed, belonging to 10 genera. The most diverse genera were Ocoaxo Fennah with 16 species and Prosapia Fennah with 8. Aeneolamia Fennah includes 3 species and 1 subspecies, Iphirhina Fennah and Neaenus Fowler 3 species each, Microsargane Fowler and Olcotomaspis Lallemand 2 species each, and Mahanarva Distant, Huaina Fennah and Zulia Fennah 1 species each. This is the first complete compilation of the Cercopidae recorded for Mexico.